Defining biodiverse reforestation: Why it matters for climate change mitigation and biodiversity. Issue 1 (20th September 2022) - Andres, Samantha E.; Standish, Rachel J.; Lieurance, Paige E.; Mills, Charlotte H.; Harper, Richard J.; Butler, Don W.; Adams, Vanessa M.; Lehmann, Caroline; Tetu, Sasha G.; Cuneo, Peter; Offord, Catherine A.; Gallagher, Rachael V.
Societal Impact Statement: Mixed species plantings present an attractive alternative to monoculture reforestation through their added benefits to biodiversity. Yet there is ambiguity in the use of the term 'biodiversity' in carbon and biodiversity markets, which may create perverse outcomes when designing schemes and projects. Here, we review how the concept of biodiversity is defined and applied in reforestation projects, and restoration more broadly. Improved transparency around the use of the term biodiversity is urgently needed to provide rigour in emerging market mechanisms, which seek to benefit the environment and people. Summary: Reforestation to capture and store atmospheric carbon is increasingly championed as a climate change mitigation policy response. Reforestation plantings have the potential to provide conservation co‐benefits when diverse mixtures of native species are planted, and there are growing attempts to monetise biodiversity benefits from carbon reforestation projects, particularly within emerging carbon markets. But what is meant by 'biodiverse' across different stakeholders and groups implementing and overseeing these projects and how do these perceptions compare with long‐standing scientific definitions? Here, we discuss approaches to, and definitions of, biodiversity in the context of reforestation for carbon sequestration. Our aim is to review how the concept of biodiversity is defined and applied among stakeholders (e.g., governments, carbon certifiers and farmers) and rights holders (i.e., First Nations people) engaging in reforestation, and to identify best‐practice methods for restoring biodiversity in these projects. We find that some stakeholders have a vague understanding of diversity across varying levels of biological organisation (genes to ecosystems). While most understand that biodiversity underpins ecosystem functions and services, many stakeholders may not appreciate the difficulties of restoring biodiversity akin to reference ecosystems. Consequently, biodiversity goals are rarely explicit, and project goals may never be achieved because the levels of restored biodiversity are inadequate to support functional ecosystems and desired ecosystem services. We suggest there is significant value in integrating biodiversity objectives into reforestation projects and setting specific restoration goals with transparent reporting outcomes will pave the way for ensuring reforestation projects have meaningful outcomes for biodiversity, and legitimate incentive payments for biodiversity and natural capital accounting. Abstract : Mixed species plantings present an attractive alternative to monoculture reforestation through their added benefits to biodiversity. Yet there is ambiguity in the use of the term 'biodiversity' in carbon and biodiversity markets, which may create perverse outcomes when designing schemes and projects. Here, we review how the concept of biodiversity is defined and applied in reforestation projects, and restoration more broadly. Improved transparency around the use of the term biodiversity is urgently needed to provide rigour in emerging market mechanisms, which seek to benefit the environment and people. Abstract : Las repoblaciones forestales con especies mixtas presentan una alternativa atractiva a las repoblaciones monoespecíficas para el secuestro de carbono con beneficios adicionales para la biodiversidad. Sin embargo, la ambigüedad en el uso del término "biodiversidad" entre las diferentes partes interesadas y la falta de conocimiento y comprensión de los complejos ecosistemas forestales pueden impedir que estas iniciativas alcancen los resultados deseados. El objetivo de nuestra investigación es identificar las principales áreas de mejora en los futuros programas de reforestación. La mejora en la definición de objetivos y la transparencia de los informes técnicos ayudarán a identificar los puntos de activación, con el fin incentivar la biodiversidad en los proyectos de repoblaciones forestales que tienen como objetivo el aumento del secuestro y fijación de carbono. Con ello, nuestro reto es también incentivar la inversión en futuros programas de reforestación y, a su vez, aumentar el beneficio de estas repoblaciones sobre la biodiversidad, el secuestro de carbono y los medios de vida de las partes interesadas.